Quartz forming conditions in secant veins in granodiorites of the Andean intrusive complex of the Barchans Islands (Аrgentine Islands, West Antarctic) - Naumko, I.М.; Artemenko, G.V.; Bakhmutov, V.G.; Vovk, O.P.; Теlepko, L.F.; Sakhno, B.E. (Доповіді НАН України, 2018)
It is established that the growth of quartz in veins in granodiorites of the Andean intrusive complex (the Barchans Islands, West Antarctic) happened in rock crystalbearing veins of steep falling, in which the temperature difference necessary for the dissolution of massive quartz and crystallization of its transparent variety in the shape of perfectly cut crystals in central parts of secant veins was reached. The discovered enrichment of the fluid medium of the quartz crystallization with СО₂, NaCl, and ÊCl indicates a carbonatehaloid composition of quartzforming fluids, which favoured the formation of jewelry and technologically perfect crystals, possibly having piezoelectric properties similar to crystals of quartz both from rockcrystalbearing veins of the Nearpolar Ural and those synthesized under laboratory conditions. As a conclusion, the connection of quartzforming fluids and the postmagmatic processes in a granodiorite intrusion is justified, and the view of investigated quartz veins as formations of posttectonic hydrothermal stage is confirmed and expanded. Bстановлено, що ріст жильного кварцу в гранодіоритах андського інтрузивного комплексу (острови Бархани, Західна Антарктида) здійснювався у кришталеносних жилах крутого падіння, в яких досягався перепад температури, необхідний для розчинення масивного кварцу і кристалізації його прозорого різновиду у вигляді прекрасно огранених кристалів у центральних частинах січних жил. Виявлена збагаченість флюїдного середовища кристалізації кварцу СО₂, NaCl і КCl вказує на карбонатно-галоїдний склад кварцутворювальних флюїдів, що сприяло формуванню ювелірно і технологічно досконалих кристалів, можливо, з п'єзоелектричними властивостями, подібно до кристалів кварцу, як кришталеносних жил Приполярного Уралу, так і синтезованих у лабораторних умовах. У підсумку обгрунтовано зв'язок кварцутворювальних флюїдів та постмагматичних процесів у гранодіоритовій інтрузії і підтверджено та розвинено точку зору на вивчені кварцові жили як на утворення посттектонічної гідротермальної стадії. Установлено, что рост жильного кварца в гранодиоритах андского интрузивного комплекса (острова Барханы, Западная Антарктида) осуществлялся в хрусталеносных жилах крутого падения, в которых достигался перепад температуры, необходимый для растворения массивного кварца и кристаллизации его прозрачной разновидности в виде прекрасно ограненных кристаллов в центральных частях секущих жил. Выявленнoe обогащениe флюидной среды кристаллизации кварца СО₂, NaCl и КCl указывает на карбонатно-галоидный состав кварцобразующих флюидов, что способствовало формированию ювелирно и технологически совершенных кристаллов, возможно, с пьезоэлектрическими свойствами, подобно кристаллам кварца, как хрусталеносных жил Приполярного Урала, так и синтезированных в лабораторных условиях. В итоге обоснована связь кварцобразующих флюидов и постмагматических процессов в гранодиоритовой интрузии и подтверждена и развита точка зрения на изученные кварцевые жилы как на образования посттектонической гидротермальной стадии.